1470 Consenting for a Bedside Procedure: A Prospective Observational Analysis of Consenting Practice in the Surgical Emergency Admissions Unit of a District General Hospital. (12th October 2021) - Davis, H; Mishra, S; Balakumar, C; Shrestha, A
Abstract: Aim: Consent is necessary to enable patient autonomy, and it is vital that it is voluntary, informed and, where possible, the patient has valid mental capacity to give consent. Recent case law has grown around consent and practice guidance has evolved. This was a prospective observational study investigating the quality of consenting practice for incision and drainage procedures performed within the surgical emergency admissions unit (SEAU) at a district general hospital. Method: A prospective study was conducted on consent documentation for a study period from August to September 2020, for patients undergoing bedside incision and drainage (I&D) procedures within the SEAU. Documentation was reviewed and data collected for quality of consent. Further data into the quality of this documentation was also collected; including legibility, risk and benefit discussions, local anaesthetic used, operation note documentation and discussion of the procedure. This was compared against GMC standards. Results: Of 20 cases (n = 20), 1 case had written consent and 15 cases had verbal consent documented. 4 cases had no documentation of consent. No cases had benefit documentation, and 4 out of the 20 cases had risks documented. 4 cases had documentation of procedure discussion. 13 cases had an operation note included. Conclusions: This study highlights a deviation from recommended practice, and results have been communicated at a departmental level. Recommendations have been offered in an attempt to improve compliance, including the display of posters in the SEAU. We shall re-audit practice within the coming months after these changes have been implemented.